Chuankezhi injection for asthma: Protocol of a systematic review and meta-analysis. Issue 33 (August 2019) - Li, Meichen; Zheng, Wenjiang; Zhang, Chaoyuan; Yan, Qian; Peng, Zijing; Xie, Fuqi; Hong, Yu; Liu, Xiaohong
Abstract: Background: Asthma is a chronic inflammatory disease characterized by recurrent attacks of breathlessness and wheezing, which often worsen at night or in the early morning and vary from person to person in severity and frequency. Chuankezhi injection (CKZ), as a new Chinese medicine, was recently found to have a good clinical effect on asthma. Whereas neither systematic nor meta-analysis of randomized controlled trials (RCTs) explain the efficacy of CKZ in treating asthma. Therefore, we provide a protocol to evaluate the efficacy and safety of CKZ for asthma. Methods: From inception until April 2019, a systematic and comprehensive literature search will be conducted in both 4 Chinese databases and 3 English databases. RCTs will be included related to CKZ for asthma. We will assess the quality of the included trials in accordance with the risk of bias tools in Cochrane manual 5.1.0. We will use the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method to assess the certainty of the estimated evidence. Data analysis will be performed using the STATA 15.0. Results: This systematic review aims to assess the effectiveness and safety of CKZ for the treatment of asthma, in order to provide evidence for the clinical practice of Chinese medicine. This protocol will be conducted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) statement. The results of this meta-analysis will be submitted to a peer-reviewed journal once it is completed. Conclusion: The consequence of this study will furnish proof to evaluate if CKZ is effective in the treatment of asthma. PROSPERO registration number: ROSPERO CRD42019134458.